Phased array probes for air-coupled ultrasonic testing based on cellular polymer - Mate Gaal; Daniel Hufschläger; Dirk Gohlke; Matthias Weise; Detlef Ilse; Wolfgang Hillger; Artur Szewieczek (Research and Review Journal of Nondestructive Testing, 2023)
Air-coupled ultrasonic testing is an established alternative to conventional ultrasonic methods for testing of light-weight components in aerospace and automotive industry. Compared to direct coupled contact technique or immersion technique it is less invasive, so that it offers numerous financial incentives. While phased arrays are already an industrial standard in fluid-coupled mechanized ultrasonic testing, air-coupled testing is usually performed using two single-element probes and a transmission technique. Therefore, advantages of phased arrays such as active focussing and manipulation of the incidence angle are rarely used with air-coupled testing. This paper presents a newly developed air-coupled phased array device with the emphasis on the characterization of the probes. The device consists of a linear array probe, a transmitter unit and a receiver unit. The main novelty is that the array probe is based on high-voltage excitation of charged cellular polypropylene. Charged cellular polymers are referred to as ferroelectrets or as piezoelectrets. They exhibit an extremely low stiffness and acoustic impedance, so that a matching layer is not necessary. Extremely low mechanical cross-coupling enables independent excitation of the elements of the array. The development of the phased array probes is supported by computations of the sound field using point source synthesis. The main intended applications are transmission with focussing, transmission with an electronic sweep and testing with air-coupled guided waves by using beam steering, applied to carbon-fibre-reinforced plates and similar materials. Air-coupled guided waves enable testing of objects with one-sided access. This work was funded from the “Technologietransfer-Programm Leichtbau” by the German Federal Ministry for Economic Affairs and Climate Action, project 03LB1001A.